DETERMINATION OF LAND TO POND RATIO IN RAIN WATER HARVESTING SYSTEM TO SUPPORT RICE-SOYBEAN CROPPING PATTERN - Hadinata, Wira (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
The rain water harvesting system consists of a land area cultivated with rice and soybean cropping patternannually, and a rainwater collection pond. Surpluswater (runoff) in raining season is captured and collected inthe pond, and used for irrigation in the following cultivation. The objective of this researchwas to determine theoptimumratio of the landto pond area. This researchwas carriedout in the IntegratedField Laboratory, Facultyof Agriculture, University of Lampung by using data of soil physical properties (water content, field capacity,permanentwilting point, percolation); rice crop coefficient, soybean crop coefficient and climatological data for13 years from1999 to 2011. Datawas processed using asimulation program(Visual Simulation)presented inthegraphical form. The results showed that the rainwater potential that can be utilized as an alternative irrigationis abundant, about 1500 mm/year - 3000 mm/year with a total of rainwater reaching 314.509,78 m3 over 13years. Based on the simulation, the most effective period of planting, for rice is in January and for soybean is inMay. In addition, the optimum pond dimension to serve 1 ha cropping land is about 2450 m2 in with 3m depth,or the ratio of land to pond is 4:1.Keywords : Evapotranspiration,Pond,Rainwater harvesting,Rice and Soybean